HUBUNGAN KOMUNIKASI INTERNAL TERHADAP KINERJA PEGAWAI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN KAMPAR INTERNAL COMMUNICATION RELATIONSHIP TO THE EMPLOYEE PERFORMANCE OF POPULATION AND CIVIL REGISTRATION DISTRICT KAMPAR - Bima Syahputra; Evawani Elysa Lubis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The organization is a container from a group of people who held a collaboration to achieve common goals. The success of organization can be realized if every individual in the organization have the performance against organization. In addition in an organization of the communication also has an important role. A better communication in the structure of can give rise to a sense of the solidarity and loyalty between employees with an organization / the institution concerned. The aim of this research is to find out how significant a strong relationship between internal communication with the employee performance in conducting the duty of department population and civil registration in Kampar.Methods used in this research namely quantitative methods with explanation survey, researchers collected data using a questionnaire. The location of this research is in the population and civil registration district Kampar. The number of samples for this research as many as 56 respondents, the withdrawal of the sample use quotas sampling techniques. To know how much the relationship between both side variables, researchers used moment products correlation analysis. While the questionnaire to data processing conducted using the product of service solution statistic ( spss ) 20.0 version for windows.This research result indicates that the relationship between internal communication with the employee performance department of population and civil registration district Kampar , Obtained t value of 0.674 which means the amount included in a category strong interprets a correlation coefficient in accordance in the guidebooks. This shows that internal communication correlation with the employee performance run well on the office of population and civil registration district Kampar. This indicates that, vertical communication and communication horizontally synchronization in these agencies showed that the percentage is a good enough, so can increase the employee performance .Thus H0 were rejected and Ha accepted.Keywords: Internal Communication, Employee Performance, Population And Civil Registration District Kampar